The Influence of Content Exposure and Information Quality on Instagram @dr. Tirta towards a Healthy Lifestyle (Study on Followers of dr. Tirta's Instagram Account) - Salsabila, Chairunada Haifa; Fatoni, Ahmad (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The research objective to be achieved in this study is to determine the influence of content exposure and the quality of information on dr. Tirta’s Instagram towards a healthy lifestyle (study on followers of dr. Tirta's Instagram account). The research object taken in this research is the followers of dr. Tirta. The theory used in this research is the stimulus organism response (S-O-R) theory. The research was conducted using a quantitative approach using non-probability sampling techniques with a population of 2.5 million followers of dr. Tirta and a sample of 400 respondents obtained from calculation results using the Slovin formula. The subjects in this research were Instagram followers of dr. Tirta. The results of this research indicate that the content exposure variable and the information quality variable on dr. Tirta’s Instagram has an influence on the healthy lifestyle of dr. Tirta’s followers.